KEBHINEKAAN DAN PERSATUAN PERSPEKTIF TAFSIR NUSANTARA - Fitri Dewi Oktafia dan Moh. Jufriyadi Sholeh (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
The diversity of race, ethnicity, language, religion or culture is the sunnahtullah which must be used as a reference for mutual understanding, complement and embrace each other, so that there is unity not a split which neither party wanted. Unity can create a strong and unbreakable nation. This research will examine in depth the diversity and unity with the perspective of the Interpretation archipelago. In this research used a qualitative approach with the type of literature review namely by using a thematic method which is descriptive-comparative. This research is in the book of interpretation of the archipelago shows that all the diversity of languages, races, skin colors, religions, cultures and so on, influenced by the place where he lives, and the degree of every human being is the same what sets it apart is the quality of piety. While unity is described with the brotherhood of believers which is based on faith and heredity, strife will end in chaos, while peace with the aim of seeking divine pleasure will be blessed.